Determinants of Takaful and conventional insurance demand: A regional analysis - Waheed Akhter; Saad Ullah Khan (Cogent Economics & Finance, 2017)
In this study, we focused on analysing and differentiating the determinants of conventional insurance and Takaful demand across ASEAN and Middle East Regions. We used panel data econometrics on a sample of 14 Asian countries having both conventional insurance and Takaful over the period 2005-2014. We applied fixed and random effect regression models to assess the impact of macroeconomic and demographic factors on conventional insurance and Takaful demand. Income and financial sector were found to have significant positive impact on insurance demand across all regions. On the other hand, dependency ratio was found to be negatively affecting Takaful demand across all regions while inflation shows positive impact. Urbanization was found to be significant positive impact on both conventional insurance and Takaful demand. Financial sector development positively triggers the insurance and Takaful demand across ASEAN region, while it triggers conventional insurance demand only in Middle East Region. Education shows negative impact on Takaful demand across both regions while it shows positive impact on insurance demand in Middle East. The study recognises the key role of urbanization and education in creating awareness to enhance Takaful demand in large populated countries of ASEAN and South Asia.
Keywords: G15; G22; J11; N45; O18; 330; Takaful (Islamic Insurance) conventional insurance; middle east; ASEAN